Engineering and application of synthetic nar promoter for fine-tuning the expression of metabolic pathway genes in Escherichia coli - Hwang, Hee Jin; Lee, Sang Yup; Lee, Pyung Cheon (Biotechnology for Biofuels, 2018)
Background: Promoters regulate the expression of metabolic pathway genes to control the flux of metabolism. Therefore, fine-tuning of metabolic pathway gene expression requires an applicable promoter system. In this study, a dissolved oxygen-dependent nar promoter was engineered for fine-tuning the expression levels of biosynthetic pathway enzymes in Escherichia coli. To demonstrate the feasibility of using the synthetic nar promoters in production of biochemicals in E. coli, the d-lactate pathway consisting of one enzyme and the 2,3-butanediol (BDO) pathway consisting of three enzymes were investigated. Results: The spacer sequence of 15 bp between the - 35 and - 10 elements of the upstream region of the wild-type nar promoter was randomized, fused to the GFP gene, transduced into E. coli, and screened by flow cytometry. The sorted synthetic nar promoters were divided into three groups according to fluorescence intensity levels: strong, intermediate, and weak. The selected three representative nar promoters of strong, intermediate, and weak intensities were used to control the expression level of the d-lactate and 2,3-BDO biosynthetic pathway enzymes in E. coli. When the ldhD gene encoding d-lactate dehydrogenase was expressed under the control of the strong synthetic nar promoter in fed-batch cultures of E. coli, the d-lactate titers were 105.6 g/L, 34% higher than those using the wild-type promoter (79.0 g/L). When the three 2,3-BDO pathway genes (ilvBN, aldB, and bdh1) were expressed under the control of combinational synthetic nar promoters (strong-weak-strong) in fed-batch cultures of E. coli, the titers of 2,3-BDO were 88.0 g/L, 72% higher than those using the wild-type promoter (51.1 g/L). Conclusions: The synthetic nar promoters, which were engineered to have strong, intermediate, and weak intensities, were successfully applied to metabolic engineering of d-lactate and 2,3-BDO pathways in E. coli. By controlling expression levels of d-lactate and 2,3-BDO pathway enzymes using the synthetic nar promoters, the production of d-lactate and 2,3-BDO was increased over that using the wild-type promoter by 34 and 72%, respectively. Thus, this synthetic promoter module system will support the improved production of biochemicals and biofuels through fine-tuning of gene expression levels.
Keywords: 2 ,3-butanediol; 35 and -10 elements; Biosynthetic pathway; D-lactate dehydrogenase; Fluorescence intensities; Gene expression levels; Lactate; nar promoter; 2,3-Butanediol; Lactate; nar promoter; Oxygen-dependent promoter; Promoter engineering